CHALLENGES AND SOLUTIONS IN THE DEVELOPMENT OF EXTRACURRICULAR ACTIVITIES ENGLISH CLUB - Aviana Aviana (JEE (Journal of English Education), 2025)
This study examines the management of the English Club extracurricular program at MTs Darul Ulum, recognizing its growing importance as a complementary space for developing twenty-first-century English proficiency. Although English Clubs are widely acknowledged in the literature as effective platforms for communicative practice, motivation building, and confidence enhancement, research focusing on their managerial processes—particularly in Islamic secondary schools—remains limited. Addressing this gap, the present study investigates how the English Club is managed, what challenges are encountered, and what solutions are implemented within the framework of Planning, Organizing, Actuating, and Controlling (POAC). A descriptive qualitative design was employed, involving interviews with the supervising teacher, observations of club activities, and analysis of program documents. The findings indicate that the English Club operates with enthusiasm but lacks structured planning, formal organizational roles, adequate facilities, and systematic evaluation procedures. Major challenges include overcrowded membership, limited teaching personnel, uneven student motivation, and restricted institutional support. Despite these constraints, the supervisor employs several adaptive strategies such as activity-based learning, peer-assisted facilitation, and attempts to build external partnerships. The study concludes that strengthening managerial components—particularly planning, organizing, and evaluation—is essential for enhancing the sustainability and pedagogical impact of the English Club. These findings provide practical implications for schools seeking to improve extracurricular language programs in resource-limited settings.